Rapid detection methods for viable Mycobacterium avium subspecies paratuberculosis in milk and cheese - Botsaris, George; Slana, Iva; Liapi, Maria; Dodd, Christine E R; Economides, Constantinos; Rees, Catherine; Pavlik, Ivo (My University, 2010)
Mycobacterium avium subsp. paratuberculosis (MAP) may have a role in the development of Crohn's disease in humans via the consumption of contaminated milk and milk products. Detection of MAP from milk and dairy products has been reported from countries on the European continent, Argentina, the UK and Australia. In this study three different methods (quantitative real time PCR, combined phage IS900 PCR and conventional cultivation) were used to detect the presence of MAP in bulk tank milk (BTM) and cheese originating from sheep, goat and mixed milks from farms and products in Cyprus. During the first survey the presence of MAP was detected in 63 (28.6%) of cows' BTM samples by quantitative real time PCR. A second survey of BTM used a new combined phage IS900 PCR assay, and in this case MAP was detected in 50 (22.2%) samples showing a good level of agreement by both methods. None of the herds tested were known to be affected by Johne's disease and the presence of viable MAP was confirmed by conventional culture in only two cases of cows BTM. This suggests that either rapid method used is more sensitive than the conventional culture when testing raw milk samples for MAP. The two isolates recovered from BTM were identified by IS1311 PCR REA as cattle and sheep strains, respectively. In contrast when cheese samples were tested, MAP DNA was detected by quantitative real time PCR in seven (25.0%) samples (n=28). However no viable MAP was detected when either the combined phage IS900 PCR or conventional culture methods were used.
Keywords: Culture; Decontamination; Food safety; Milk; PCR; Real time PCR